A Review of Factors Influencing the Seagrass-Sea Cucumber Association in Tropical Seagrass Meadows - Floren, Adonis S.; Hayashizaki, Ken-ichi; Putchakarn, Sumaitt; Tuntiprapas, Piyalap; Prathep, Anchana (Frontiers in Marine Science, 2021)
In the tropical ecosystem, sea cucumbers are associated with seagrass meadows in various ways, often forming a network of ecological interactions. From this myriad of interactions, the trophic relationship between the seagrasses and sea cucumbers has received recent attention with the advent of analytical techniques. However, little is understood about the exact mechanism by which seagrasses are sustaining the sea cucumber populations in the food chain, considering the high number of refractory components in seagrasses and the lack of digestive enzymes among sea cucumbers. This manuscript aims to review existing concepts in ecology concerning the association between tropical seagrasses and sea cucumbers to provide directions for research and management of this vital resource. We searched literature from electronic databases and identified key concepts concerning sea cucumber and seagrass communities based on geographic distribution, nutrient compositions, seagrass decomposition process, and trophic enrichments in the food chain. A conceptual model was then developed detailing the factors influencing the association between the seagrass meadows and sea cucumbers. Despite the limited published information on the seagrass–sea cucumber association, a synthesis of the current understanding of this topic is provided to address the declining sea cucumber populations in the tropical seagrass meadows. We suggest that the successful restoration of sea cucumber fisheries requires a thorough understanding of the seagrass decomposition process, which is vital to the diet of sea cucumbers.